Current Knowledge on Infectious Bronchitis Virus Non-structural Proteins: The Bearer for Achieving Immune Evasion Function - Peng, Shuwei; Wang, Yiming; Zhang, Yu; Song, Xu; Zou, Yuanfeng; Li, Lixia; Zhao, Xinghong; Yin, Zhongqiong (Frontiers in Veterinary Science, 2022)
Infectious bronchitis virus (IBV) is the first coronavirus discovered in the world, which is also the prototype of the gamma coronavirus. Nowadays, IBV is widespread all over the world and has become one of the causative agent causing severe economic losses in the poultry industry. Generally, it is believed that the viral replication and immune evasion functions of IBV were modulated by non-structural and accessory proteins, which were also considered as the causes for its pathogenicity. In this study, we summarized the current knowledge about the immune evasion functions of IBV non-structural and accessory proteins. Some non-structural proteins such as nsp2, nsp3 and nsp15 have been shown to antagonize the host innate immune response. Also, nsp7 and nsp16 can block the antigen presentation to inhibit the adapted immune response. In addition, nsp13, nsp14 and nsp16 are participating the formation of viral mRNA cap to limit the recognition by innate immune system. In conclusion, it is of vital importance to understand the immune evasion functions of IBV non-structural and accessory proteins, which could help us to further explore the pathogenesis of IBV and provide new horizons for the prevention and treatment of IBV in the future.